The rule of law “on the ground”. The Polish courts’ perspective - Podolska, Anna; Śniadach, Olga; Warylewska-Kamuś, Krystyna (Przegląd Prawniczy Uniwersytetu im. Adam Mickiewicza, 2023)
The aim of this article is to demonstrate how often and in what ways the concept of the rule of law is utilised by the Polish courts. The authors examined the case law of the Constitutional Tribunal, the Supreme Court, but above all, of the common courts, published after 1997 (the year in which the Constitution of the Republic of Poland entered into force) with regard to how often judges invoke the concept of the rule of law and how they explain it. The main idea was to capture certain tendencies, in an attempt to take a wider view rather than analyse individual rulings. It is a look “from above” adapted to determine if and how often courts refer to the concept of the rule of law and what changed in this regard after 2015, when the systematic and consistent destruction of the judicial system began. Analysis of the judicial decisions of the common courts, whose actions are especially important for the individual, are the focal point. It is in these courts that majority of cases are settled, as they are the closest to the citizen. Of course, the common courts do not act in isolation and so the judicial activity of the Constitutional Tribunal and the Supreme Court was also examined. However, rulings of those entities are frequently subject to in-depth analysis, so the focus was placed only on examining regularities in their invoking the concept of the rule of law. Since the Constitutional Tribunal and – to a certain degree – the Supreme Court have been captured by the ruling political group, entailing that the authorities have destroyed judicial independence, it is worthwhile to concentrate on the common courts, as they could possibly be representing the last bastions of an independent justice system.